REFLEKSI NAFS DALAM KISAH NABI YUSUF AS DAN ZULAIKHA: ANALISIS TAFSIR AL-MISHBAH KARYA QURAISH SHIHAB - M. Sulhan; Eva Latipah (Tajdid: Jurnal Pemikiran Keislaman dan Kemanusiaan, 2022)
The story of the Prophet Yusuf as ahsanul qashas (the best story) which is enshrined in the Qur'an. The story of the Prophet Yusuf is a story that has a wealth of meaning and learning in all aspects of life. This article attempts to analyze the richness of meaning contained in surah Yusuf which is related to the levels and expressions of the nafs. The research method in this article uses descriptive qualitative with a library research approach. Theoretical analysis uses the perspective of Tafsir Al-Mishbah by Quraish Shihab. The purpose of this research is to answer how the expression of nafs and levels of nafs are contained in the story of Prophet Yusuf and Zulaikha. The results of the study show that the nafs in the story of Prophet Yusuf and Zulaikha are distinguished by two tendencies: First, the level of anger in Zulaikha's personality and behavior which is depicted in obedience to lust and following the devil's temptations. Second, the levels of muthmainnah and radhiyah nafs in Yusuf's personality which are described by calm, obedience, peace, and fortitude in going through every test given by Allah SWT. The study in this research is limited to the story of persuasion planned by Zulaikha.